Cardiac Output Monitoring in Preterm Infants - McGovern, Matthew; Miletin, Jan (Frontiers in Pediatrics, 2018)
Maintaining optimal circulatory status is a key component of preterm neonatal care. Low cardiac output in the preterm neonate leads to inadequate perfusion of vital organs and has been linked to a variety of adverse outcomes with heightened acute morbidity and mortality and adverse neurodevelopmental outcomes. Having technology available to monitor cardiac output allows us to detect low-output states and potentially intervene to mitigate the unwanted effects of reduced organ perfusion. There are many technologies available for the monitoring of cardiac output in the preterm neonatal population and while many act as useful adjuncts to aid clinical decision-making no technique is perfect. In this review, we discuss the relative merits and limitations of various common methodologies available for monitoring cardiac output in the preterm neonatal population. We will discuss the ongoing challenges in monitoring cardiac output in the preterm neonate along with current gaps in our knowledge. We conclude by discussing emerging technologies and areas that warrant further study.